2011
DOI: 10.2139/ssrn.2239023
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Age and the Second Globalization in Italy

Abstract: After the Golden Age, Italy experienced increasing difficulties in adjusting its economy to the changing external context and to the requirements for sustaining catch-up growth at a higher level of economic development. The adjustment issue is common to advanced countries but the difficulties experienced in Italy look particularly severe. Cushioned by inflation and devaluation, growth remained relatively high in the 1970s. In the subsequent decade, in spite of improved conditions for addressing macroeconomic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Middle class families were few, and they did employ servants to care for children and elderly. Authors have showed how especially in the aftermath of the Second World War, domestic care for the elderly was severely transformed due to strong industrialization and new employment opportunities (Crafts and Magnani 2011). Domestic care for the elderly performed by migrant workers was also a sign of social mobility among Italian employers (Catanzaro and Colombo 2004).…”
Section: The Context Of Eldercare and Romanian Migrant Domestic Workementioning
confidence: 99%
See 1 more Smart Citation
“…Middle class families were few, and they did employ servants to care for children and elderly. Authors have showed how especially in the aftermath of the Second World War, domestic care for the elderly was severely transformed due to strong industrialization and new employment opportunities (Crafts and Magnani 2011). Domestic care for the elderly performed by migrant workers was also a sign of social mobility among Italian employers (Catanzaro and Colombo 2004).…”
Section: The Context Of Eldercare and Romanian Migrant Domestic Workementioning
confidence: 99%
“…In southeast Italy, starting with the 1960s and 1970s women started to work in the local textile and tobacco industries. The women who were employed during the 'golden age of post-war Italian growth' (Crafts and Magnani 2011) represented to a large extent the 'golden generation' of Italian light industry. Women started to gain constant money, which represented an unprecedented financial security for their households.…”
Section: The Context Of Eldercare and Romanian Migrant Domestic Workementioning
confidence: 99%
“…In turn, this process continually disrupts established interests, throwing up the risk that at some point they may succeed in halting the process of reform, causing economic growth to falter. 30 The core issue of socialist economic reform was the possibility of nesting the advantages of decentralized markets within the structures of socialist state regulation. 31 It was sometimes thought that centralized planning had worked well in the early years of so-called extensive growth, and needed reform only after industrial modernization.…”
Section: Reformsmentioning
confidence: 99%
“…Nicholas Crafts and Gianni Toniolo, 'Aggregate growth, 1950-2005,' in Stephen Broadberry and Kevin H. O'Rourke, eds, The Cambridge Economic History of Modern Europe, vol. 2 (Cambridge: Cambridge University Press, 2010), 303.…”
mentioning
confidence: 99%
“…Globalisation fostered a reorganisation of production worldwide by encouraging firms to locate phases of production in different countries in order either to exploit lower factor costs or to boost their ability to penetrate the new (emerging) markets. 2 For a discussion of these imbalances in an historical perspective, see Crafts and Magnani (2013). 3 The Maastricht criteria for admission in the EMU were (i) an inflation rate no more than 1.5 percentage points above the average of the three countries with the lowest inflation rates; (ii) nominal long-term interest rates not exceeding by more than 2 percentage points those of the three countries with the lowest interest rates; (iii) no exchange rate realignment for at least two years; and (iv) a government budget deficit not exceeding 3 per cent of GDP and a gross debt-to-GDP ratio not above 60 per cent, or "sufficiently diminishing and approaching the reference value at a satisfactory pace".international division of labour (Confindustria, 1997) and enabled the country to join the EMU, they did not prevent the trend of Italian productivity falling below the European average since the mid-1990s.…”
Section: Policy Issues and Priorities At The Start Of Emumentioning
confidence: 99%